Lo : poems - Crowe, Melissa (Iowa poetry prize., 2023)
"Lo maps the deprivation and richness of a rural girlhood and offers an intimate portrait of the woman-tender, hungry, hopeful-who manages to emerge. In a series of lyric odes and elegies, Lo explores the notion that we can be partially constituted by lack-poverty, neglect, isolation. The child in the book's early sections is beloved and lonely, cherished and abused, lucky and imperiled, and by leaning into this complexity, the poems render a tentative and shimmering space sometimes occluded, the space occupied by a girl coming to find herself and the world beautiful, even as that world harms her. As the speaker comes of age, the collection asks a set of interrelated questions: What kind of life can a subject build when her early experiences give rise to dissociation? What kinds of stories can we tell when trauma robs us of memory and language? What paths might lead toward liberation from the foundational constraints of heteronormativity, capitalism, and violence? And how can such liberation be managed or maintained against the backdrop of political upheaval, climate catastrophe, and pandemic? To these questions, the book attempts a set of answers, all of which involve love and desire as compensatory forces. While their speaker often finds herself in mourning, afraid, and unsure of who and how to trust, the poems in Lo seek modes of survival and even joy, a way to tell the truth about suffering (her own and other's) while claiming the solace and delight available in friendship, sex, marriage, and the natural world"--